Inequality and the Covid crisis in the United Kingdom - Richard W. Blundell; Mónica Costa Dias; Jonathan Cribb; Robert Joyce; Tom Waters; Thomas Wernham; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2022)
We review the effects on the Covid-19 pandemic on inequalities in education, the labour market, household living standards, mental health, and wealth in the UK. The pandemic has pushed up inequalities on several dimensions. School closures particular disrupted the learning of poorer children, leading to lower attainment. Mental health worsened for those groups (women and younger adults) who had poorer mental health pre-pandemic. Lockdowns and social distancing particularly reduced the ability of younger, lower-earning, and less educated people to work. However, job-support programmes combined with the expanded welfare system meant that, if anything, disposable income inequality fell. Rising house prices have benefited people in particular around the middle of the wealth distribution. In the longer term, lower work experience for the less educated and missed schooling could push up some inequalities. Increased rates of working from home seem likely to persist which may increase some inequalities and decrease others.
Keywords: 330; inequality; Covid-19 pandemic; education; living standards; wealth